Implicit leadership theory among Malaysian managers: Impact of the leadership expectation gap on leader-member exchange quality. - Sambasivan, Murali; Subramaniam, Anusiya; Othman , Rozhan (Emerald, 2010)
Purpose: This paper aims to examine implicit leadership theory (ILT) among Malaysian managers and the impact of the gap between the ILT and actual leader behavior on leader-member exchange (LMX) quality. Design/methodology/approach: A survey of 137 Malaysian managers working under the supervision of Malaysian and Japanese superiors in five Japanese multi-national corporations (MNCs) in Malaysia was conducted to test the hypotheses of this study. Findings: The results reveal that there is a distinct Malaysian ILT. It also found that there are differences in the ILT of different ethnic groups in Malaysia. Contrary to expectations, there is no significant difference in the leadership expectation gap among managers reporting to superiors from the same background compared to superiors from a different nationality and ethnic background. Duration of managers' relationship with their superior have a moderating effect on the relationship between leadership expectation gap and LMX quality. Practical implications: The findings of this study can serve practitioners in organizational and leadership development by contributing to the awareness that ILT affects the quality of a leader's exchange within his or her followers. Originality/value: This paper contributes to the literature by providing a first insight on ILT in the Malaysian context, particularly on the variation across the main ethnic groups in the country.